Development of Information System Optimization Methods Based on Wavelet Canonical Expansions and Wavelet Neural Network Technologies - Igor Sinitsyn; Vladimir Sinitsyn; Eduard Korepanov; Tatyana Konashenkova (Современные информационные технологии и IT-образование)
Canonical expansion (CE) of stochastic processes (StP) are widely used in applied mathematics, informatics and control. Based on wavelet computing technologies, the authors developed the theory of wavelet canonical decompositions (WCDE), as well as the theory of canonical decompositions based on a wavelet neural network (WNNN). In the report, after a brief review of the development of the theory of canonical expansions, wavelet-canonical expansions and the theory of canonical expansions based on a wavelet neural network, a method for synthesizing an optimal information system based on the energy criterion (EC) is considered. Problem statement is given for V.S. Pugachev IS and WCDE. WCDE is constructed of CE of input StP. Equations for EC-optimal operator are presented. Formulae for mathematical expectation and variance of EC-optimal output StP estimate are outlined. Illustrate example confirms effective of suggested method in comparison with other two known methods.